On the Characterization of Behavior-Driven Development Adoption Benefits: A Multiple Case Study - Couto, Thiciane; Marczak, Sabrina; Callegari, Daniel; Móra, Michael; Gomes, Fabio (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2022: Anais do XXI Simpósio Brasileiro de Qualidade de Software, 2022)
BDD supports software development teams in building and delivering user needs. Although the claims that BDD adoption improves product and software processes, there is still no consolidated evidence about its benefits nor have we found quality indicators to measure them. This paper reports on a study that aimed to identify and characterize the benefits of BDD adoption in software teams novice to it. We conducted a multiple case study in teams formed by students working with industry practitioners in active-based learning programs. Perceived benefits are improved communication, faster delivery cycles, better product quality, among others. Each benefit was characterized into aspects that express how the benefit is conceptualized. For instance, improved communication is perceived by sharper conversations with the product owner. Our results might inspire both practitioners and scholars in the pursuit of quality indicators to measure the benefits of adopting BDD.